2019
DOI: 10.3389/fnins.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Nerve Stimulation Attenuates Ischemia-Reperfusion Induced Retina Dysfunction in Acute Ocular Hypertension

Abstract: Purpose: The present study aimed to investigate whether cervical vagal nerve stimulation (VNS) could prevent retinal ganglion cell (RGC) loss and retinal dysfunction after ischemia/reperfusion (I/R) injury.Methods: First, rats were randomly divided into sham group (n = 4) and VNS group (n = 12). Activation of the nodose ganglia (NOG), nucleus of the solitary tract (NTS), superior salivatory nucleus (SSN), and pterygopalatine ganglion (PPG) neural circuit were evaluated by c-fos expression at 0 h after sham VNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Inoue et al have found that stimulation of vagal afferents or efferents 24 h before renal ischemia markedly attenuated AKI and decreased systemic inflammation depending on α7 nicotinic acetylcholine receptor-(α7nAChR-) positive splenocytes [19]. In addition, VNS has been applied to treat I/R injury-induced inflammation and oxidative stress in multiple organs [11,16,19]. The VNS treatment in this study effectively ameliorated renal injury caused by I/R by reducing systemic inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Inoue et al have found that stimulation of vagal afferents or efferents 24 h before renal ischemia markedly attenuated AKI and decreased systemic inflammation depending on α7 nicotinic acetylcholine receptor-(α7nAChR-) positive splenocytes [19]. In addition, VNS has been applied to treat I/R injury-induced inflammation and oxidative stress in multiple organs [11,16,19]. The VNS treatment in this study effectively ameliorated renal injury caused by I/R by reducing systemic inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, the left cervical vagosympathetic trunks of the rats were separated and stimulated (frequency 20 Hz, 0.1 ms duration) through a pair of TeflonR-coated silver wires (0.1 mm in diameter) with a special stimulator (S20, Jinjiang, Chengdu, China). The voltage necessary to achieve a 10% reduction in sinus rate was used as the threshold [11,16]. The VNS treatment was performed throughout the I/R process.…”
Section: Vns Treatmentmentioning
confidence: 99%
“…Notably, atVNS did not promote significant changes in c-Fos density in any of the thirty (fifteen per hemisphere) brain regions studied. Other previous reports found changes in c-Fos density after the electrostimulation, particularly an increase in the number of c-Fos+ cells, in areas of the brainstem (Huffman et al, 2019 ; Jiang et al, 2019 ; Katagiri et al, 2019 ). However, all these studies used percutaneous or invasive VNS approaches, or applied the stimulation longer times.…”
Section: Discussionmentioning
confidence: 82%
“…VIP has been reported to protect retinal ganglion cells against glutamate excitotoxicity in vitro [178] and to reduce the retinal neurodegenerative effect of ischemia–reperfusion injury through an antioxidant action [179]. VIP may also mediate the reduction of t e inflammatory response and the improvement of retinal function induced by vagal stimulation in rats with acute ocular hypertension [180]. Recently, both PACAP and VIP have been shown to efficiently attenuate ischemic retinal degeneration induced by bilateral common carotid artery occlusion (BCCAO) when are bound to the cell penetrating peptide TAT and administered through eye drops [181].…”
Section: Vasoactive Intestinal Peptide and Pituitary Adenylate Cycmentioning
confidence: 99%